807 Wellens syndrome: a rare entity not to underestimate. (8th December 2021) - Calderone, Dario; Mauro, Maria Sara; Legnazzi, Marco; Agnello, Federica; Scalia, Lorenzo; Greco, Antonio; Capodanno, Davide; Tamburino, Corrado
Abstract: Aims: Abrupt oppressive chest pain is a common reason of emergency department's access. An accurate assessment of the clinical setting is needed to ensure the patient the correct management. This includes a good anamnesis, physical examination, electrocardiogram (ECG) and cardiac biomarkers evaluation. Wellens syndrome is a clinical entity characterized by acute chest pain, normal or minimal elevation of cardiac biomarker, specific ECG changes with no ST elevation or Q-waves. The ECG modifications contemplate: biphasic T waves in lead V2 and V3 (type A) initially positive and subsequent negative or deep and symmetrically inverted T waves in anterior leads (Type B, more often V1–V4). Recognizing these patterns can be so challenging for physician in emergency departments, especially in Type A, and failure in diagnosis can lead to deleterious outcomes. In fact, Wellens syndrome can be considered as a pre-infarction state that needs immediate intervention: if not treated appropriately, about 75% of patients can suffer anterior myocardial infarction due to a stenosis of left anterior descending (LAD) artery. Methods: A 55-year-old male with hyperlipidaemia and a family history of cardiovascular disease, presented to emergency department with abrupt oppressive chest pain after mild physical effort. At presentation he presented a typical ECG of Wellens syndrome type A with negative cardiac biomarkers. His GRACE (Global Registry of Acute Coronary Events) score was 72 and his thrombolysis in myocardial infarction (TIMI) was 2. At second blood sample cardiac biomarkers was mildly higher than upper limit of normal. Results: Despite low grade on risk stratification he immediately underwent coronary angiography, who resulted in a subocclusive stenosis from ostium to the medium tract of LAD. PCI was subsequently taken with implantation of TWO drug eluting stent (DES). After 3 days he was discharged asymptomatic and in optical medical therapy. Conclusions: Wellens syndrome is a rare clinical entity that must be considered as a pre- infarction state difficult to individuate. Conventional management in these patients utilizing typical risk stratification scores may not be appropriate. In this context an early diagnosis of ECG patterns it's crucial, in order to provide an urgent percutaneous intervention. Failure in recognition of signs and symptoms of Wellens syndrome can lead to disastrous outcome due to a critical, vulnerable, stenosis on proxymal LAD and to a possible imminent large anterior myocardial infarction.